1993
DOI: 10.1055/s-0038-1649646
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies Enhance Thrombin-Induced Platelet Activation and Thromboxane Formation

Abstract: SummaryIn a group of 6 patients with lupus anticoagulant (LA) and antiphospholipid (aPL) antibodies detected by ELISA ovemight urine and blood were simultaneously collected. A significantly increased urinary excretion of the platelet-derived thromboxane (TX) metabolite 11-dehydro-TXB2 was found in this group, as compared to 12 healthy individuals. In contrast, a small but significant reduction of the vascular prostacyclin (PGI2) metabolite 2,3-dinor-6-keto-prostaglandin F1α was observed.To further elucidate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
1
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(78 citation statements)
references
References 37 publications
5
70
1
2
Order By: Relevance
“…The prothrombotic properties of aPL may be explained in part by their ability to enhance the activation of platelets. Moreover, aPL have been shown to increase production of TXB 2 in the presence of low doses of ADP, collagen, or thrombin (7,10,26,27). A recent study by our group showed a significant increase in the expression of activated glycoprotein IIb/IIIa on platelets treated with aPL and TRAP (8).…”
Section: Discussionmentioning
confidence: 89%
“…The prothrombotic properties of aPL may be explained in part by their ability to enhance the activation of platelets. Moreover, aPL have been shown to increase production of TXB 2 in the presence of low doses of ADP, collagen, or thrombin (7,10,26,27). A recent study by our group showed a significant increase in the expression of activated glycoprotein IIb/IIIa on platelets treated with aPL and TRAP (8).…”
Section: Discussionmentioning
confidence: 89%
“…31) Studies indicate that aCL antibodies are not generated by tissue necrosis but rather that they participate in the pathogenesis of MI. 4,30) This hypothesis is biologically plausible because of the inflammatory 8,32,33) and procoagulant [34][35][36] properties of these antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that part of the effect of aspirin on thrombosis prophylaxis in APLA patients relies on platelet thromboxane inhibition. It has been shown that the urine of APLA patients has increased quantities of thromboxane metabolites [26,27] and that purified APLA increase platelet thromboxane production after minimal thrombin stimulation in vitro [28]. However, the ability of APLA to activate platelets directly is still debated, since, for example, incubation with APS sera resulted in an increase of platelet-associated IgG without any clear activation in one study [29].…”
Section: Discussionmentioning
confidence: 99%